Law Enforcement Against Perpetrators of Domestic Violence in terms of Legislation and Islamic Law - Fathul Djannah; Muhammad Rizal (Britain International for Academic Research (BIAR) Publisher, 2020)
The aims of the study is to find out the law enforcement against perpetrators of domestic violence in terms of legislation and islamic law. this research was conducted by examining library materials or secondary data relating to divorce on the grounds of domestic violence. Furthermore, using a normative juridical approach, it is intended to get clarity about divorce on the grounds of domestic violence. The result shows that the criminal law policy in the formulation of a system of criminal sanctions against perpetrators of a crime in domestic violence according to the provisions of the Domestic Violence Act (UUPKDRT) uses an alternative formulation system type. Criminal sentences in the form of imprisonment or fines with minimum and maximum rules. In Article 44 (physical violence), Article 45 (psychological violence), and Article 49 (neglect) there is no stipulation of a criminal minimum limit that only mentions a maximum limit